Development, Implementation, and Assessment of a Genetics Curriculum Across Institutions - Sarah Dotters-Katz; Ginger Hocutt; C Michael Osborne; Emily E. Hardisty; Laurie Demmer; Neeta Vora (Thieme Medical Publishers, Inc., 2016)
Abstract Objective Many residency programs offer limited exposure and minimal didactic time genetics, despite its frequent use in obstetrics and gynecology. The objective of this study was to develop, pilot, and assess a three-module women's health genetics curriculum for residents that was easily transferable between institutions. Methods An interactive three-module genetics curriculum covering basic principles, prenatal screening/diagnosis, and cancer genetics was developed. A pre- and posttests were used to assess improvement in knowledge. Subjective feedback was obtained to assess curricular satisfaction. The data were analyzed with descriptive statistics. Results The curriculum was administered at two institutions. Forty-eight residents attended ≥ 1 session. Twenty completed the pretest, and 23 completed the posttest. At the first institution, using audience response system, the percentage correct per question increased on 10/14 questions between pre- and posttests. All students felt the curriculum was useful and would strongly recommend to other residents. At the second institution, pre/posttests were distributed on paper. Mean scores significantly improved between pre- and posttests (p = 0.007). On the pretest, no residents scored > 70%. However, 8/13 scored > 70% on the posttest (p = 0.002). Instructors at both institutions described the curriculum as easy to use/implement. Conclusion This three-module workshop on women's health genetics was easily implemented across institutions and led to increased knowledge.